Veneer grafting for successful Tamarind propagation - Shankarprasad, K S; Menon, Jalaja S (Indian Horticulture, 2021)
Tamarind, the most widely used acidulent spice or condiment in Indian subcontinent. In the recent years it has gained lot of importance worldwide and now it’s not just remained as a mere food ingredient of kitchen, but rather became one of the important commodity being exported from India in wide arrays of form like, pulp concentrate, seed kernal powder, dried pulp, etc. Being drought hardy, tamarind is one of the promising crop for regions with frequent drought and low rainfall for climate resilient sustainable agriculture. Being perennial in nature, tamarind seedling origin trees takes 8-12 years for bearing fruits. To overcome this problem, vegetative propagation is the only way. Hence vegetative propagation is evaluated to standardise the method and time of propagation to meet the demand for quality planting material for commercial cultivation and also for growing in kitchen garden to meet the demands of households.